2011
DOI: 10.1075/sic.8.1.03cla
|View full text |Cite
|
Sign up to set email alerts
|

Restricciones pragmáticas y sociales en la expresión de futuridad en el español de Puerto Rico

Abstract: Restricciones pragmáticas y sociales en la expresión de futuridad en el español de Puerto RicoJeroen Claes y Luis Ortíz López En español, la futuridad se puede expresar mediante cuatro paradigmas verbales: el futuro morfológico, el futuro perifrástico, el presente de indicativo y el presente continuo. La investigación realizada sobre el fenómeno (Iuliano ) postula que la variación no es libre y que las variantes presentan una distribución diferente debido a su semantismo propio y a factores extralingüísticos. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 2 publications
0
5
0
2
Order By: Relevance
“… 12 An anonymous reviewer suggested that perhaps the ongoing change in pronoun use begins in the Caribbean and then is accelerated in the NYC contact setting, which is arguably the case for the increasing use of the periphrastic construction to express futurity (Orozco 2007; Claes & Ortiz López 2011). If we apply this line of thinking to pronoun use in NYC, then the women effect among Cubans could perhaps be traced back to Cuba and, therefore, attributed to the common situation in monolingual settings where women lead change.…”
Section: Notesmentioning
confidence: 99%
“… 12 An anonymous reviewer suggested that perhaps the ongoing change in pronoun use begins in the Caribbean and then is accelerated in the NYC contact setting, which is arguably the case for the increasing use of the periphrastic construction to express futurity (Orozco 2007; Claes & Ortiz López 2011). If we apply this line of thinking to pronoun use in NYC, then the women effect among Cubans could perhaps be traced back to Cuba and, therefore, attributed to the common situation in monolingual settings where women lead change.…”
Section: Notesmentioning
confidence: 99%
“…The effect of certainty in previous research indicated that the MF is a marker of uncertainty (Blas Arroyo 2008) and the PF is a marker of either certainty (Gudmestad and Geeslin 2011, NS group) or neither certainty nor uncertainty (Claes and Ortiz López 2011) in Spanish NSs. L2 learners in Gudmestad and Geeslin (2011) were not sensitive to this variable.…”
Section: Discussionmentioning
confidence: 94%
“…With respect to temporal distance, previous research seemed to converge on the PF as the form that is not marked for temporal distance, the PI as the close future form, and the MF as the distant future form (Blas Arroyo 2008;Claes and Ortiz López 2011;Díaz-Campos and Escalona Torres 2018;Gudmestad and Geeslin 2011;Kanwit 2021;Kanwit and Solon 2013). For both groups in the current study, the results regarding the PF and PI were similar and reflected the trend previously attested in the literature.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations